KAPITALISASI DEMOKRASI DAN JARINGAN PATRONASE POLITIK (KETERLIBATAN PENGUSAHA TAMBANG DALAM PILKADA DI KALIMANTAN SELATAN) - M. Uhaib As’ad (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2016)
This paper explain the conspiracy and involvement boss mine (coal) in several provincial elections (regents and governors) in South Kalimantan. As is known, the political landscape of post Soeharto New Order government that gave birth to democracy and radical change in the institutions of power, namely from the centralized power-authoritarian system to a democratic system of government has spawned a democratic transition prolonged until today. In the midst of a prolonged transition to democracy at this time, the arena of democracy has been hijacked and the stage of political and economic power has been controlled by entrepreneurs or local and national capitalist power by doing pesekongkolan between candidates authorities or local authorities that one of them through the local election process. The businessmen are involved as a supplier of funds to the local authorities candidat candidate to win as a form of money politics and transactional politics. In some cases the local elections in South Kalimantan, such as the election of the regent and the governor, political practice as it was very clear and has already become a political culture that is structured and massive post-New Order government.